2022
DOI: 10.3390/toxics10080417
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Polycyclic Aromatic Hydrocarbons: A Systematic Mapping and Review of Neuropathological Mechanisms

Abstract: Several studies present the neurotoxic effects of polycyclic aromatic hydrocarbons (PAHs), a class of environmental pollutants capable of causing neurological deficits. However, a collective review approach to this research topic is scarce. This study presents the effect of PAHs on the central nervous system using a bibliometric approach. The neuropathological mechanisms of PAHs are also highlighted. Published articles were searched for in the Scopus and Web of Science databases from January 1979 to December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 97 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…It is known that some pathways of aryl-hydrocarbon neurotoxicity are common for PAHs, TCDD, dioxin-like agents, polyphenols, and similar xenobiotics. A review of the neuropathological mechanisms of PAHs highlights that these, together with their metabolites, may cross the blood–brain barrier causing neurological abnormalities that may include neuronal damage, impaired neurotransmitter regulation, parasympathetic dysregulation, and neurodegeneration ( 65 ). Preclinical studies hint at a common neuropathological mechanism of PAH action being the binding of these compounds to the aryl-hydrocarbon receptor (AhR), a cytosolic transcription factor that initiates a complex pathway leading to alteration of gene regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that some pathways of aryl-hydrocarbon neurotoxicity are common for PAHs, TCDD, dioxin-like agents, polyphenols, and similar xenobiotics. A review of the neuropathological mechanisms of PAHs highlights that these, together with their metabolites, may cross the blood–brain barrier causing neurological abnormalities that may include neuronal damage, impaired neurotransmitter regulation, parasympathetic dysregulation, and neurodegeneration ( 65 ). Preclinical studies hint at a common neuropathological mechanism of PAH action being the binding of these compounds to the aryl-hydrocarbon receptor (AhR), a cytosolic transcription factor that initiates a complex pathway leading to alteration of gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies hint at a common neuropathological mechanism of PAH action being the binding of these compounds to the aryl-hydrocarbon receptor (AhR), a cytosolic transcription factor that initiates a complex pathway leading to alteration of gene regulation. AhR is also present in neural cells and can be involved in the mechanisms leading to PAH-induced neurological disorders ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brain endothelial cells are less permeable to chemicals, but PAHs and their derivatives are highly lipophilic compounds that can cross the blood−brain barrier and reach the brain. PAHs and the derivatives are neurotoxic, especially B[a]P. 170 Studies have reported that in differentiated human neuroblastoma SKN-SH cell lines, both parent PAHs and APAHs including dibenzothiophene and retene produce neurotoxicity in a concentration-dependent manner, and APAHs are more toxic than parent PAHs. 171 After acute exposure to 9,10-phenanthrenequinone in T. obscurus, four metabolic pathways are affected, and the 9,10phenanthrenequinone induced oxidative stress and causes neurotoxicity in fish.…”
Section: Other Toxicitiesmentioning
confidence: 99%
“…These compounds have the potential to accumulate in the human body and induce carcinogenic, teratogenic, and mutagenic effects (Figure 2). Several studies have demonstrated that PAHs have adverse effects on various physiological systems, including the respiratory system (Leachi et al., 2020), circulatory system (Korashy & El‐Kadi, 2006), nervous system (Olasehinde & Olaniran, 2022), as well as the liver and kidney.…”
Section: Influence Of Anthocyanins On Contaminants From Food Processingmentioning
confidence: 99%